RELEVANCE OF MACHINERY SLAUGHTERING OF ANIMALS IN THE MODERN ERA IN A REVIEW OF ISLAMIC LAW - Raja Ritonga; Siti Aminah (Kopertais Wilayah X Jawa Tengah, 2023)
Food and drink are two things that everyone needs. However, for a Muslim, halal food and drinks are always a priority. Therefore, not all food and drinks are halal for consumption, such as the halalness of animals or animals. Islamic teachings teach that the halal and unlawful slaughter of animals is closely related to the method of slaughtering them. This article explains and describes the relevance of slaughtering animals using cutting machines in the modern age. This research uses a qualitative method type of literature study. The data used in this study came from the search results of some books, MUI fatwas, articles, and others related to research. Furthermore, the data were analyzed descriptively using a normative approach. The results of the study explain that the slaughter of animals using a slaughter machine is considered valid if it meets the requirements set out in the MUI fatwa’s.